The FAST Globular Cluster Pulsar Survey (GC FANS) - Yujie Lian; Zhichen Pan; Haiyan Zhang; Shuo Cao; P. C. C. Freire; Lei Qian; Ralph P. Eatough; Lijing Shao; Scott M. Ransom; Duncan R. Lorimer; Dejiang Yin; Yinfeng Dai; et al. (The Astrophysical Journal Supplement Series)
By 2025 January, 60 pulsars were discovered by the Five-hundred-meter Aperture Spherical radio Telescope globular cluster (GC) pulsar survey (GC FANS), with spin periods spanning 1.98–3960.72 ms. Of these, 55 are millisecond pulsars (MSPs; P  < 30 ms), while 35 are binaries with orbital periods spanning 0.12–466.47 days. This paper describes GC FANS, a deep, thorough search for pulsars in 41 GCs in the FAST sky (−14° <  δ  < 65°), and describes new discoveries in 14 of them. We present updated timing solutions for M92A, NGC 6712A, M71A, and M71E, all of which are “spider” pulsars with short orbital periods. We present new timing solutions for M71B, C, and D. With orbital periods of ∼466 and 378 days, M71B and M71C are the widest known GC binaries; these systems resemble the normal wide MSP-He WD systems in the Galactic disk. With a spin period of 101 ms, M71D is in an eccentric ( e  ∼ 0.63) orbit with an 11 day period and a massive companion; the system has a total mass of 2.63 ± 0.08 M _⊙ . These features and its large characteristic age suggest it is a double neutron star system (DNS) formed via massive binary evolution early in the cluster’s history, akin to Galactic disk DNSs—unlike other candidate GC DNSs, which typically form dynamically. A comparative analysis of GC pulsar populations within FAST’s sky reveals that most clusters (10 of 14) resemble the Galactic disk MSP population, likely due to lower stellar densities.